A função de orientador argumentativo dos rótulos em artigo de opinião : uma questão de entonação de valores sociais - Oliveira, Gisele de Freitas Paula (2011)
In the light of the sociointeractionist perspective, this study has as main objective to research the referentiation process through labels, that is to say, nominal expressions that summarize sections of the text, pointing the function of argumentative guiding performed by these expressions. According to this theoretical perspective, we understand that reality is constructed throughout our social and discursive practices. Thus, instead of conceiving that the relation between language and world is in a direct and specular way, we hold “the public versions of the world” (MONDADA & DUBOIS, 2003[1995]). In order to achieve the aim of this research, we will consider Bakhtin’s philosophical concept of valuation (BAKHTIN, 1993[1920-24]). By doing so, we want to show that the subject selects the linguistic forms that are best suited to what he projected to say. The subject does it while constructs the discourse object. However, this same subject is not alone when he makes these choices; on the other hand, he is singular and social, simultaneously, he rejects and takes different social values, the ones that determine the form and content of his enunciation. The texts utilized to exemplify us discussion in this study are three opinion articles published by columnists from Espírito Santo (a State in the Southeast) in A Gazeta newspaper, which ones were selected from August through December 2009. We took a dialogic attitude in order to clarify that the position taken by the columnist in the construction of the discourse object was dialogic, because it responds to other statements and points an assessment that does not emanate from a single subject, but social. Thereby, we believe that the labels’ function as argumentative guiding is better understood if we consider the dialogic system in which these expressions occur.